Bergey's Manual of Systematics of Archaea and Bacteria 2015
DOI: 10.1002/9781118960608.gbm00904
|View full text |Cite
|
Sign up to set email alerts
|

Ehrlichia

Abstract: Ehr.lich' i.a . M.L. fem. n. Ehrlichia named after Paul Ehrlich, a German bacteriologist. Proteobacteria / Alphaproteobacteria / Rickettsiales / Anaplasmataceae / Ehrlichia Coccoid to ellipsoidal cells . Found in cytoplasmic vacuoles in endothelial or hemopoietic mammalian host cells , including macrophages, monocytes, neutrophils, and cells of the bone marrow, liver, spleen, or lymph nodes. Ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Ehrlichia genus is composed of obligate intracellular Gram-negative pleomorphic tick-borne bacteria, which infect a wide range of host cells, including endothelial and hemopoietic cells (e.g., macrophages and neutrophils), in which they form clusters known as morulae [ 149 ]. To date, Ehrlichia chaffeensis , Ehrlichia ewingii , and Ehrlichia muris subsp.…”
Section: Ehrlichiamentioning
confidence: 99%
See 1 more Smart Citation
“…Ehrlichia genus is composed of obligate intracellular Gram-negative pleomorphic tick-borne bacteria, which infect a wide range of host cells, including endothelial and hemopoietic cells (e.g., macrophages and neutrophils), in which they form clusters known as morulae [ 149 ]. To date, Ehrlichia chaffeensis , Ehrlichia ewingii , and Ehrlichia muris subsp.…”
Section: Ehrlichiamentioning
confidence: 99%
“…Nevertheless, novel species are continuously being detected from several animal hosts. It is likely that some of these may have a zoonotic potential [ 149 , 150 , 151 ]. On the other hand, several authors have suggested that Ehrlichia canis , a pathogen of dogs, may also be linked to human disease [ 152 ]; however, to date, this is still controversial, and more studies are needed to clarify it.…”
Section: Ehrlichiamentioning
confidence: 99%